Improvement of fiber connectivity and functional recovery after stroke by montelukast, an available and safe anti-asthmatic drug. (April 2019) - Gelosa, Paolo; Bonfanti, Elisabetta; Castiglioni, Laura; Delgado-Garcia, José Maria; Gruart, Agnès; Fontana, Lucia; Gotti, Marco; Tremoli, Elena; Lecca, Davide; Fumagalli, Marta; Cimino, Mauro; Aigner, Ludwig; et al.
Graphical abstract: Abstract: Stroke is one of the main causes of death, neurological dysfunctions or disability in elderly. Neuroprotective drugs have been proposed to improve long-term recovery after stroke, but failed to reach clinical effectiveness. Hence, recent studies suggested that restorative therapies should combine neuroprotection and remyelination. Montelukast, an anti-asthmatic drug, was shown to exert neuroprotection in animal models of CNS injuries, but its ability to affect oligodendrocytes, restoring fiber connectivity, remains to be determined. In this study, we evaluated whether montelukast induces long-term repair by promoting fiber connectivity up to 8 weeks after middle cerebral artery occlusion (MCAo), using different experimental approaches such as in vivo diffusion magnetic resonance imaging (MRI), electrophysiological techniques, ex vivo diffusion tensor imaging (DTI)-based fiber tracking and immunohistochemistry. We found that, in parallel with a reduced evolution of ischemic lesion and atrophy, montelukast increased the DTI-derived axial diffusivity and number of myelin fibers, the density of myelin binding protein (MBP) and the number of GSTpi + mature oligodendrocytes. Together with the rescue of MCAo-induced impairments of local field potentials in ischemic cortex, the data suggest that montelukast may improve fibers reorganization. Thus, to ascertain whether this effect involved changes of oligodendrocyte precursor cells (OPCs) activation and maturation, we used the reporter GPR17iCreERT2:CAG-eGreen florescent protein (GFP) mice that allowed us to trace the fate of OPCs throughout animal's life. Our results showed that montelukast enhanced the OPC recruitment and proliferation at acute phase, and increased their differentiation to mature oligodendrocytes at chronic phase after MCAo. Considering the crosstalk between OPCs and microglia has been widely reported in the context of demyelinating insults, we also assessed microglia activation. We observed that montelukast influenced the phenotype of microglial cells, increasing the number of M2 polarized microglia/macrophages, over the M1 phenotype, at acute phase after MCAo. In conclusion, we demonstrated that montelukast improves fiber re-organization and long-term functional recovery after brain ischemia, enhancing recruitment and maturation of OPCs. The present data suggest that montelukast, an already approved drug, could be "repositioned "as a protective drug in stroke acting also on fiber re-organization.